RINITIS ALERGI DI POLIKLINIK THT-KL BLU RSU PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI 2010 – DESEMBER 2012 - Reinhard, Elia; Palandeng, O. I.; Pelealu, O. C. P. (e-CliniC, 2013)
ABSTRACT: Allergic Rhinitis is an atopic condition which most often occurred. The incidence of allergic rhinitis is estimated at about 10% of the general population. This study aims to know the profile of allergic rhinitis patients in Ear, Nose and Throat – Head and Neck Surgery Department at Prof. Dr. R. D. Kandou General Hospital, Manado period January 2010 – December 2012 by using descriptive retrospective study method. The overall number of objects in this study are 209 patients. The result, distribution by year obtained the highest number of patients in the year 2011 as many as 80 patients of 4.295 visitors (1,86%), age group 21-30 years old had the highest percentage (23,92%). Percentage of patients with allergic rhinitis was higher in woman (56,48%) than men (43,54%), jobs of patients which employees have highest percentage (34,93%), sneezing clinical symptom has highest percentage (39,40%), antihistamine treatment has highest percentage (42.70%). Conclusion, Age group 21-30 years is the most frequent suffer from allergic rhinitis. Woman is more frequent suffer from allergic rhinitis than in men. The job of patients which most frequent to get allergic rhinitis is an employee. Clinical symptoms which are most frequent complained are sneezing, rhinorrhea and nasal congestion. Treatment which most frequent given is antihistamine drug. Keywords: Allergic rhinitis   ABSTRAK: Rinitis alergi merupakan keadaan atopi yang paling sering dijumpai. Insiden rinitis alergi diperkirakan menyerang sekitar 10% dari populasi umum. Penelitian ini dilakukan untuk mengetahui profil penderita rinitis alergi di poliklinik THT-KL BLU RSU Prof. Dr. R. D Kandou Periode Januari 2010 – Desember 2012 dengan menggunakan metode retrospektif deskriptif. Keseluruhan jumlah objek penelitian adalah 209 penderita. Hasil penelitian, distribusi menurut tahun didapatkan jumlah penderita tertinggi pada tahun 2011 yaitu sebanyak 80 penderita dari 4.295 pengunjung (1,86%),  golongan umur 21-30 tahun memiliki presentase tertinggi (23,92%). Rinitis alergi tinggi pada perempuan (56,48%) dari pada laki-laki (43,54%), pekerjaan terbanyak adalah pegawai (34,93%), gejala klinik bersin sebesar 39,40%,  penanganan antihistamin memiliki presentase tertinggi sebesar 42.70%.Kesimpulan, golongan umur 21-30 tahun ialah yang paling sering menderita rinitis alergi. Perempuan lebih sering menderita rinitis alergi daripada laki-laki. Jenis pekerjaan yang paling sering terkena rinitis alergi ialah pegawai. Gejala klinik yang paling sering dikeluhkan yaitu bersin-bersin, rinore dan hidung tersumbat. Penanganan yang paling sering diberikan ialah obat golongan antihistamin. Kata Kunci: Rinitis alergi